2008
DOI: 10.1371/journal.pone.0002044
|View full text |Cite|
|
Sign up to set email alerts
|

Dental Microwear and Diet of the Plio-Pleistocene Hominin Paranthropus boisei

Abstract: The Plio-Pleistocene hominin Paranthropus boisei had enormous, flat, thickly enameled cheek teeth, a robust cranium and mandible, and inferred massive, powerful chewing muscles. This specialized morphology, which earned P. boisei the nickname “Nutcracker Man”, suggests that this hominin could have consumed very mechanically challenging foods. It has been recently argued, however, that specialized hominin morphology may indicate adaptations for the consumption of occasional fallback foods rather than preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
250
7
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(276 citation statements)
references
References 30 publications
(44 reference statements)
13
250
7
6
Order By: Relevance
“…Stable carbon isotope analyses indicate that A. africanus had a diet that was isotopically mixed (e.g., 17), and the dental microwear on A. africanus molars indicates a varied diet consisting of a low incidence of hard foods, relatively nonresistant foods, and those that are displacement-limited (14) like tough vegetation (18). Dental microwear patterns in other ''gracile'' and some ''robust'' australopiths exhibit even less evidence of hard object feeding (19,20), and none of the australopiths exhibit the extreme variability in microwear characterized by primates that seasonally exploit underground storage organs (19) like tubers. Among early hominins, only Paranthropus robustus exhibits microwear consistent with the regular and/or seasonal consumption of stress-limited foods (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable carbon isotope analyses indicate that A. africanus had a diet that was isotopically mixed (e.g., 17), and the dental microwear on A. africanus molars indicates a varied diet consisting of a low incidence of hard foods, relatively nonresistant foods, and those that are displacement-limited (14) like tough vegetation (18). Dental microwear patterns in other ''gracile'' and some ''robust'' australopiths exhibit even less evidence of hard object feeding (19,20), and none of the australopiths exhibit the extreme variability in microwear characterized by primates that seasonally exploit underground storage organs (19) like tubers. Among early hominins, only Paranthropus robustus exhibits microwear consistent with the regular and/or seasonal consumption of stress-limited foods (18).…”
Section: Resultsmentioning
confidence: 99%
“…However, microwear-based evidence suggesting that hard foods were rare or absent in the diets of most australopiths is seemingly difficult to reconcile with dietary interpretations based on mechanics and comparative anatomy (2,3,6,(19)(20)(21). Thus, it has been suggested that, in some species, hard objects may have been ''fallback'' foods (i.e., less desirable foods that are eaten only when other preferred resources are not available [e.g., 22]) that were selectively important but infrequently consumed and thus may have influenced morphological evolution without leaving a microwear signal (19,20). This hypothesis is viable but is difficult to test because it is based on negative evidence.…”
Section: Resultsmentioning
confidence: 99%
“…between certain distantly related taxa), but to document differences in diet when they might not necessarily be expected based on tooth morphology alone. Differences between closely related taxa have been captured, for instance, in bovids (Scott, 2012; Ungar, Merceron, & Scott, 2007), cervids (Berlioz, Kostopoulos, Blondel, & Merceron, 2017), ungulates (Schulz, Calandra, & Kaiser, 2010), feliforms (DeSantis & Haupt, 2014; DeSantis, Tseng, et al, 2017), canids (DeSantis et al, 2015), primates (Scott et al, 2005; Ungar, Grine, & Teaford, 2008), and macropodids (DeSantis, Field, Wroe, & Dodson, 2017; Prideaux et al, 2009). Indeed, many bioarchaeological studies have demonstrated distinctive and predictable diet‐related differences in both gross dental wear and microwear within a single species, Homo sapiens (Rose & Ungar, 1998).…”
mentioning
confidence: 99%
“…These findings are at odds with evidence from dental microwear, which tend to support consumption of non-fracture resistant foods [189,190,191]. Here we examine how the isotopic composition of simulated foragers can be influenced by energetic reserves and enamel volume over a lifespan by incorporating carbon isotope ratios as a function of foraging decisions into the forward iteration algorithm (see Appendix 4.1).…”
Section: Informing Paleo-dietary Evidencementioning
confidence: 99%
“…Isotopic evidence shows these animals to have diets influenced by C 4 -photosynthetic plants (e.g. tropical grasses or sedges -or potentially animals that consumed these plants) [175,191], which tend to be fracture resistant, however patterns of molar microwear indicate a diet of softer, less fracture resistant foods [189,190]. Importantly, the isotopic composition of molar enamel forms early in life whereas patterns of microwear are recorded later in life, such that the potential influence of life-history stages cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%